Foundations of Financial Management - Block, Stanley B. (New York, 2015)
Thirty-two years have passed since we began writing the first edition of this text, and many things have changed during that time. First of all, the field of finance has become much more analytical, with the emphasis on decision-oriented approaches to problems rather than the old, descriptive approach. We have increased the use of analytical approaches to financial problems in virtually every chapter of the book. But we also have stayed with our basic mission of making sure the student is able to follow us in our discussions throughout the text. While the 13th edition is considerably more sophisticated than the initial edition, it is still extremely “reader friendly.” As the analytical skills demanded of students have increased, so has the authors’ care in presenting the material...